Analisis Dampak Strategi Pemasaran Digital Terhadap Pertumbuhan Bisnis Startup - Akhmad Mubadilah; Haris Karyadi; Evi Sirait; Krisna Meidiyantoro B.; Mohammad Gifari Sono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to analyze the impact of digital marketing strategies on the growth of startup businesses. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that there are several positive impacts of digital marketing on the growth of startup businesses, namely first, digital marketing allows startup businesses to reach a wider audience globally, not limited to geographical boundaries. By using tools such as SEO (Search Engine Optimization) and content marketing. Second, it allows startup businesses to interact directly with potential customers through various online communication channels such as social media, email, and direct conversations. Third, it helps startup businesses to achieve their marketing goals, increase revenue, build brand awareness, and strengthen relationships with customers.